Assessing age discrimination in workplaces: psychometric exploration of the Workplace Age Discrimination Scale (WADS-G) - Funk, Maria; Lorenz, Timo (Frontiers in Psychology, 2024)
In contemporary workplaces characterized by diverse age groups working collaboratively, the assessment of age discrimination as an interpersonal phenomenon has gained heightened significance. This study focuses on adapting and scrutinizing the psychometric properties of the German iteration of the Workplace Age Discrimination Scale (WADS-G). Comprehensive Confirmatory Factor Analysis (CFA) results affirm a robust fit for the unidimensional model. Convergent validity is established through correlations between WADS-G scores and related instruments, while discriminant validity is evidenced by its lack of association with extraversion. Noteworthy findings include a positive correlation with turnover intention and negative correlations with job satisfaction, occupational self-efficacy, and organizational affective commitment. Despite its merits, the predictive efficacy of the WADS-G is notably inferior when juxtaposed with the Workplace Incivility Scale. Its explanatory power for turnover intention is constrained when accounting for variables such as job satisfaction, work environment, neuroticism, and core selfevaluation. Although measurement invariance testing across gender groups reveals scalar to strict measurement invariance, the examination across age groups indicates metric invariance. However, Confirmatory Factor Analyses for the 18-30 and 50+ age groups, central to the research emphasis, reveal suboptimal model fit. These outcomes prompt a nuanced discussion on whether the WADS-G aptly captures age-discriminatory experiences across diverse age and gender cohorts among employees.